THE EFFECT OF CAPITAL INTENSITY, EXECUTIVE CHARACTERISTICS, AND SALES GROWTH ON TAX AVOIDANCE - Levana Dhia Prawati; Jessica Pinta Uli Hutagalung (Bina Nusantara University, 2020)
This study aims to examine and obtain empirical evidence about the effect of capital intensity, executive character, and sales growth on tax avoidance in Indonesia public listed consumer goods industry companies over the period of 2016-2018. Using a purposive sampling method, the sample selected in this study is 30 companies. This study uses multiple linear regression analyses to examine the effect of independent variables on the dependent variable. This study shows that capital intensity and executive characteristics have significant effects on tax avoidance. Meanwhile, sales growth has no significant effect on tax avoidance.